Global ionospheric flare detection system (GIFDS). (February 2016) - Wenzel, Daniela; Jakowski, Norbert; Berdermann, Jens; Mayer, Christoph; Valladares, Cesar; Heber, Bernd
Abstract: The Global Ionospheric Flare Detection System (GIFDS) is currently under development at the German Aerospace Center as a ground based detector for continuous monitoring of the solar flare activity in order to provide real time warnings on solar X-ray events. GIFDS is using Very Low Frequency (VLF) radio transmissions in the northern hemisphere which respond to enhanced ionization in the bottomside ionosphere caused by X-ray flares. Since solar flares can only be detected during daytime, VLF receivers have to be installed around the globe to guarantee continuous records at the dayside sector. GIFDS consists of a network of Perseus SDR (Software Defined Radio) receivers equipped with a MiniWhip antenna each. Reliable detection of solar flares is ensured by recording multiple frequency channels ranging from 0 to 500 kHz. The applicability of the system is demonstrated in a first analysis by comparing VLF measurements with GOES's (Geostationary Operational Environmental Satellite) X-ray flux data. The high potential of GIFDS for a permanent monitoring of solar flares in near real time is discussed. Abstract : Highlights: Development of a ground based continuous monitoring of the dayside lower ionosphere. VLF amplitude and phase measurements for solar X-ray flare detection. Model of active flare observation time slot depending on position and solar radiation.